2009
DOI: 10.3168/jds.2008-1545
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the effect of oral selenium supplementation on milk selenium concentration in cattle

Abstract: Soils in many regions of the world have a low Se content. Consequently, forages and crops grown on these soils may provide inadequate dietary Se for humans and grazing animals. Selenium supplementation has been used to enhance Se status and milk Se concentration, but results conflict. Milk Se concentration appears to be a useful indicator of animal and herd Se status, and reflects the responsiveness to supplementation. A systematic review and meta-analysis were carried out to summarize all available scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 74 publications
4
66
0
3
Order By: Relevance
“…In our results, the correlation was not significant (P=0.06), even if a tendency was observed. However, by comparing to the literature data in other dairy species (Ceballos et al, 2009;Davis et al, 2006), and in spite of the relative low Se status in serum, camel milk seems richer in selenium (Faye et al, 2011).…”
Section: Selenium In Milkmentioning
confidence: 84%
See 1 more Smart Citation
“…In our results, the correlation was not significant (P=0.06), even if a tendency was observed. However, by comparing to the literature data in other dairy species (Ceballos et al, 2009;Davis et al, 2006), and in spite of the relative low Se status in serum, camel milk seems richer in selenium (Faye et al, 2011).…”
Section: Selenium In Milkmentioning
confidence: 84%
“…The selenium (Se) in milk was regularly investigated in cattle (Ceballos et al, 2009) or in ewe (Davis et al, 2006), but in camel, the references remain scarce. Previous studies were mainly limited to blood status and only 3 references are available on the selenium quantity transferred through milk to the camel calf (Al-Qarawi et al, 2001;Seboussi et al, 2009a;Faye et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Silvestre et al (2007) showed an improvement in blood neutrophils phagocytosis and killing activities in dairy cows supplemented with Se-yeast (an organic source of Se) compared with those given an inorganic source of Se. It should be noted that cattle supplemented with Se-yeast had an increase in serum and milk Se concentrations in comparison with those given sodium selenite (Weiss et al 2005, Ceballos et al 2009, Cortinas et al 2010) and also lower SCC and new cases of subclinical mastitis (Cortinas et al 2010). In face of, the improvement in the microbicidal activity of milk and blood PMNL even in dairy cows with a Se-adequate status, as encountered here, is probably one reason that explain the lower incidence of mastitis and also lower SCC described by others studies.…”
Section: Discussionmentioning
confidence: 99%
“…The response to supplementation of animal diets depends on the source and dose of Se [140]. Selenium can be supplied in animal diets either as the organic or inorganic form.…”
Section: Food Fortification: Meat Milk and Eggsmentioning
confidence: 99%